Development of motor actions in young judokas: strategies for increasing efficiency - Makarov I.V. ,; Borovaya V.A. ,; Vrublevskiy E.P. , (Theory and Practice of Physical Culture, 2025)
Objective of the study was to scientifically support the application of confounding factors of both external and internal origins to enhance the performance of young judo athletes in controlling their movements. Methods and structure of the study. The research was conducted at the Igor Makarov Judo School in Gomel. The study involved 11- to 13-year-old judo athletes who participated in an eight-week pedagogical experiment. The experimental group (n=14) was subjected to additional exogenous and endogenous loads during training, while the control group (n=15) followed a standard program designed for youth schools of this age range. The assessment of the agility level of the young athletes included a series of tests that simulated movements commonly used in training and competition scenarios, both in familiar and unfamiliar environments. Results and conclusions. It was discovered that incorporating confounding factors into the training regimen of young judoists aged 11 to 13 years is a successful strategy for enhancing the specific physical exertion experienced by the participants, fostering the activation of latent capabilities and psychophysiological functions during physical activity. The examination of the outcomes demonstrated an enhancement in the experimental group's capacity to assess the time required to complete a particular task and to minimize time wastage in unforeseen circumstances, as well as an improvement in their ability to swiftly adapt their motor program and anticipate spatial and temporal changes in the environment.